1990
DOI: 10.1063/1.459584
|View full text |Cite
|
Sign up to set email alerts
|

On the electronic structure of electrides

Abstract: We explore a mechanism for the remarkable charge isolation of the localized, or trapped, electrons found in the crystalline electrides Cs(18C6)2 and Cs(15C5)2. 133Cs NMR measurements show only ≊ 0.05% atomic character of the spin density at the Cs nucleus, consistent with many features of the structure and measured properties which indicate that the localized electron distribution is centered at the anion vacancies. The optical absorption data suggest that the localized electrons, which give rise to the Curie-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Specifically, the observation was made that certain trimer configurations would form a strong dipole and the excess electron would occupy an extremely diffuse molecular orbital, localized at one end of the cluster. Note that these diffuse orbitals are very similar to the Rydberg-like states observed by Rencsok et al in theoretical studies of the Li + (9C3) 2 e – complex . Further, those configurations of the anionic water trimer possess exceptionally large hyperpolarisabilities.…”
Section: Molecular Electridessupporting
confidence: 83%
“…Specifically, the observation was made that certain trimer configurations would form a strong dipole and the excess electron would occupy an extremely diffuse molecular orbital, localized at one end of the cluster. Note that these diffuse orbitals are very similar to the Rydberg-like states observed by Rencsok et al in theoretical studies of the Li + (9C3) 2 e – complex . Further, those configurations of the anionic water trimer possess exceptionally large hyperpolarisabilities.…”
Section: Molecular Electridessupporting
confidence: 83%
“…Finally, we note the neutron diffraction study of Li(ND3) 4 [3], which found that one of the Li-N distances 0.3 -Lĩ Li(9C3)ĩ s much larger than the others (by 0.5 A). In LDA [1] this difference did not occur in the molecule, and only a small distortion of the Li-N distances occurred in the solid.…”
mentioning
confidence: 73%
“…It was argued [4 -6] that essentially similar behavior should occur for the molecules Cs(18C6)z, Cs(15C5)2, and the various alkali cryptand complexes, which are the basic molecular units of experimentally studied crystals [2]. Figure 1 shows the HOMO for Li(NH3) 4 and Li(9C3) 2, both in the Hartree-Pock approximation (HFA) [7]. The similarity of the two cases with regard to the greatly expanded HOMO is clear.…”
mentioning
confidence: 90%
See 2 more Smart Citations